Role of Inflammation in Cardiac Remodeling After Acute Myocardial Infarction - Fonseca, Francisco A.; Izar, Maria C. (Frontiers in Physiology, 2022)
Atherosclerosis is defined as an inflammatory disease. Low-grade inflammation is present in all phases of the cardiovascular continuum, since the establishment of cardiovascular risk factors and ischemic heart disease until cardiovascular events, such as myocardial infarction, heart failure and death. Not all inflammatory pathways are linked to cardiovascular outcomes, and thus, not all anti-inflammatory approaches decrease cardiovascular events. The most common cause of ventricular remodeling and heart failure is ischemic heart disease. Biomarkers such as high-sensitivity C-reactive protein can identify individuals at risk of major cardiovascular complications, but this biomarker has no causal effect on cardiovascular disease. On the other hand, interleukin 6 appears to be causally associated with cardiovascular disease. CANTOS was the first proof of concept study showing that anti-inflammatory therapy reduces major cardiovascular outcomes. Based on many anti-inflammatory trials, only therapies acting on the NLRP3 inflammasome, or interleukin 1beta, showed benefits on cardiovascular disease. Ventricular remodeling, particularly after myocardial infarction seems also influenced by the intensity of inflammatory responses, suggesting that anti-inflammatory therapies may reduce the residual cardiovascular risk. Inflammasome (NLRP3) activation, subtypes of lymphocytes, interleukin 6, and some inflammatory biomarkers, are associated with larger infarct size and impaired ventricular function after myocardial infarction. Cardiovascular risk factors commonly present in patients with myocardial infarction, and advanced age are associated with higher inflammatory activity.